Analysis of the Effect of Productive Land Area, Production Volume, Exchange Rates, and International Prices on the Volume of Indonesian Dry Natural Rubber Exports for the Period 2015-2024 - Amelia, Poppy; Aliudin, Aliudin; Sariyoga, Setiawan (Dinasti Publisher, 2026)
This research investigates the impact of productive land area, production volume, the rupiah exchange rate against the US dollar, and international prices on Indonesia's dry natural rubber export volume from 2015 to 2024. Secondary data were sourced from the Central Statistics Agency, the Ministry of Agriculture, and Bank Indonesia. The analytical approach employed multiple linear regression, incorporating classical assumption tests and hypothesis testing to validate the model. Partial results reveal that productive land area, exchange rate, and international prices exert a negative yet insignificant influence on export volume. In contrast, production volume demonstrates a positive and significant effect, underscoring that higher output can substantially boost exports. Simultaneously results the four independent variables significantly affect export volume, as evidenced by an Fvalue of 97,446 exceeding the Ftable value of 5,19 and a significance level of 0,000 below 0,05. The R² value of 0,987 suggests that 98,7% of the variation in export volume is accounted for by these factors. These findings highlight the critical role of enhancing production efficiency and implementing economic stabilization measures to improve the global competitiveness of Indonesia's rubber exports.